A task-based approach to materials design and evaluation for upper elementary Thai EFL learners - Peemmetasawad , Pinyapat; Sudajit-apa, Melada (Journal of Language and Culture, 2019)
English language teaching textbooks used in most Thai schools are grammar-driven and do not seem to support communicative skills development. This study focuses on the development and use of EFL materials that specifically aim to encourage English communication for Grade 4 students at a non-tradition school in Bangkok, Thailand. Additionally, this study intends to explore the suitability and effectiveness of the designed materials, relying on a task-based approach intertwined with Vygotsky’s Sociocultural theory to determine if they fulfill the students’ needs for communicative tasks. The designed materials were implemented with two English language classes taught by two different teachers and then evaluated through video/audio-based classroom observations, student questionnaires, as well as in-depth interviews with teachers and students. The research methodology was a mixed-method research methodology, focusing more on qualitative methods. The qualitative data from the classroom observations, teaching notes about the designed materials, open-ended questions in the questionnaires and the interviews were used to analyze task effectiveness, whereas the quantitative data was used to validate the analysis. The findings revealed that unstructured tasks were not suitable for beginner level learners. The learners had insufficient language to produce the output by themselves and relied heavily on Thai, their first language (L1) to perform the task. Moreover, the teacher’s use of L1 and English (L2) also affected how the learners acquired the target language. When the teacher in the study accommodated the learners by translating their input and instruction into Thai, the learners could understand better but faced difficulty expressing themselves in English. Therefore, when designing EFL materials for young learners, tasks should be designed to suit the learners’ language level and a teaching manual that describes a variety of appropriate feedback needs to be written for teachers to use task-based materials effectively.